Adjuvant Chemotherapy for Breast Cancer in Older Women: An Analysis of Retrospective English Cancer Registration Data. Issue 7 (July 2019) - Ward, S.E.; Holmes, G.R.; Ring, A.; Richards, P.D.; Morgan, J.L.; Broggio, J.W.; Collins, K.; Reed, M.W.R.; Wyld, L.
Abstract: Aims: Adjuvant chemotherapy is recommended as a treatment for women with high recurrence risk early breast cancer. Older women are less likely to receive chemotherapy than younger women. This study investigated the impact of chemotherapy on breast cancer-specific survival in women aged 70 + years using English registry data. Materials and methods: Cancer registration data were obtained from two English regions from 2002 to 2012 ( n  = 29 728). The impact of patient-level characteristics on the probability of receiving adjuvant chemotherapy was explored using logistic regression. Survival modelling was undertaken to show the effect of chemotherapy and age/health status on breast cancer-specific survival. Missing data were handled using multiple imputation. Results: In total, 11 735 surgically treated early breast cancer patients were identified. Use of adjuvant chemotherapy has increased over time. Younger age at diagnosis, increased nodal involvement, tumour size and grade, oestrogen receptor-negative or human epidermal growth factor receptor 2-positive disease were all associated with increased probability of receiving chemotherapy. Chemotherapy was associated with a significant reduction in the hazard of breast cancer-specific mortality in women with high risk cancer, after adjusting for patient-level characteristics (hazard ratio 0.74, 95% confidence interval 0.67–0.81). Discussion: Chemotherapy is associated with an improved breast cancer-specific survival in older women with early breast cancer at high risk of recurrence . Lower rates of chemotherapy use in older women may, therefore, contribute to inferior cancer outcomes. Decisions on potential benefits for individual patients should be made on the basis of life expectancy, treatment tolerance and patient preference. Highlights: Chemotherapy recommended for women with early breast cancer with high recurrence risk. Chemotherapy usage by age and impact on mortality explored using cancer registry data. Analysis showed lower rates of chemotherapy in patients aged 70 + years than under 70 years. Chemotherapy was associated with reduced cancer-specific mortality in aged 70 + years group. Low chemotherapy rates in older women may be adversely affecting cancer outcomes.